2004
DOI: 10.1111/j.1470-6431.2003.00340.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring physical access to ‘healthy foods’ in areas of social deprivation: a case study in Cardiff

Abstract: This paper examines some characteristics of ‘food deserts’– areas of social deprivation which have poor physical access to food shopping – in a large British city, Cardiff. The stereotype of the ‘food desert’ is critically examined, emphasizing the importance attached by residents of such areas to easy access to food shopping, especially in multiple supermarkets. The case study of Cardiff briefly discusses the identification of potential ‘food deserts’, and then examines the structures of ‘healthy food’ availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
85
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(88 citation statements)
references
References 17 publications
1
85
0
2
Order By: Relevance
“…Availability of certain types of foods, often fruits, vegetables, and low-fat dairy, in different types of stores and geographic areas has been used to determine whether local residents have access to healthful foods (Hendrickson, Smith, & Eikenberry, 2006) and how food access affects health outcomes (Inagami, Cohen, Finch, & Asch, 2006;Lane, Keefe, Rubinstein, Levandowski, Webster, Cibula, Boahene, Dele-Michael, Carter, Jones, Wojtowycz, & Brill, 2008;Wang, Kim, Gonzalez, MacLeod, & Winkleby, 2007), with the general finding that the type of store most available in a given neighborhood affects residents' body mass index. Costs of a selection of foods, usually a predetermined "healthy food basket," have also been compared by geographic or demographic area (Donkin, Dowler, Stevenson, & Turner, 2000;Guy & David, 2004;Lee, et al, 2002), demonstrating that food costs and availability often vary within one community depending on the neighborhood. One of the most complete approaches to assessing food access is to determine how far, and by what method, consumers must travel to reach particular types of food by mapping the distance from either individual residence (Algert, Agrawal, & Lewis, 2006) or neighborhood (Sharkey, Horel, & Dean, 2010) to a variety of food sources such as supermarkets, small markets, and convenience stores.…”
Section: Food System Scales and Choicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Availability of certain types of foods, often fruits, vegetables, and low-fat dairy, in different types of stores and geographic areas has been used to determine whether local residents have access to healthful foods (Hendrickson, Smith, & Eikenberry, 2006) and how food access affects health outcomes (Inagami, Cohen, Finch, & Asch, 2006;Lane, Keefe, Rubinstein, Levandowski, Webster, Cibula, Boahene, Dele-Michael, Carter, Jones, Wojtowycz, & Brill, 2008;Wang, Kim, Gonzalez, MacLeod, & Winkleby, 2007), with the general finding that the type of store most available in a given neighborhood affects residents' body mass index. Costs of a selection of foods, usually a predetermined "healthy food basket," have also been compared by geographic or demographic area (Donkin, Dowler, Stevenson, & Turner, 2000;Guy & David, 2004;Lee, et al, 2002), demonstrating that food costs and availability often vary within one community depending on the neighborhood. One of the most complete approaches to assessing food access is to determine how far, and by what method, consumers must travel to reach particular types of food by mapping the distance from either individual residence (Algert, Agrawal, & Lewis, 2006) or neighborhood (Sharkey, Horel, & Dean, 2010) to a variety of food sources such as supermarkets, small markets, and convenience stores.…”
Section: Food System Scales and Choicesmentioning
confidence: 99%
“…However, tools developed to assess general food access and the relationship between food access and health outcomes may be useful in assessing the state of LFS initiatives. Presence or absence of different types of food retailers in a particular geographic or demographic area is one indicator of access to food (Alwitt & Donley, 1997;Bodor, Rose, Farley, Swalm, & Scott, 2007;Guy & David, 2004;Lee, Darcy, Leonard, Groos, Stubbs, Lowson, Dunn, Coyne, & Riley, 2002;Morland, Wing, Diez Roux, & Poole, 2002). Availability of certain types of foods, often fruits, vegetables, and low-fat dairy, in different types of stores and geographic areas has been used to determine whether local residents have access to healthful foods (Hendrickson, Smith, & Eikenberry, 2006) and how food access affects health outcomes (Inagami, Cohen, Finch, & Asch, 2006;Lane, Keefe, Rubinstein, Levandowski, Webster, Cibula, Boahene, Dele-Michael, Carter, Jones, Wojtowycz, & Brill, 2008;Wang, Kim, Gonzalez, MacLeod, & Winkleby, 2007), with the general finding that the type of store most available in a given neighborhood affects residents' body mass index.…”
Section: Food System Scales and Choicesmentioning
confidence: 99%
“…Furey et al (2001) note that: "Food deserts …have been further exacerbated by the effect of large grocery retailers locating on the periphery of towns and the subsequent displacement effect of independent retailers in the town centre" (p.447). The development of food superstores and associated retail concentration and locational decentralisation (Burt and Sparks 2003) apparently left some areas with only limited access to affordable and healthy food (Cummins and Macintyre, 1999, 2002b, Clarke et al 2002, Rex and Blair 2003, Guy and David 2004. Cummins and Macintyre (2002a) comment: 'Popularly therefore, the major food retailers are held partly responsible for the emergence of food deserts -for not establishing shops in poor communities and so denying residents the benefits of choice and a good price' (p436).…”
Section: Healthy Cities?: the Impact Of Food Retail Led Regeneration mentioning
confidence: 99%
“…This would imply shop closures and a redistribution towards the new facility rather than a widening of food choice and accessibility. Guy David 2004) The research reported here is one strand of a larger study that evaluated the impact of a non-healthcare (i.e. hypermarket) intervention on health and diet (Cummins et al 2004).…”
Section: Healthy Cities?: the Impact Of Food Retail Led Regeneration mentioning
confidence: 99%
“…Amartya Sen observed in his work on famine and poverty, that "starvation is the characteristic of some people not 16 Data in Table 2 Access to food is comprised of three elements, namely: physical, economic, and social. Physical access is the ability to reach shops, markets or supermarkets where the required food is to be found (Guy & David, 2004). Physical impediment to access to food occurs where food is available in a country or location and there is shortage in another location due to limited or no transport facilities between both locations (FAO, 2012).…”
Section: Access To Foodmentioning
confidence: 99%